PENGARUH PEMBELAJARAN MIND MAPPING TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA PADA MAPEL IPS KELAS V SD NEGERI BUNDER IV KABUPATEN TANGERANG - Balqis Marta Lestari; Saktian Dwi Hartantri; Yoyoh Fathurrohmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of mind mapping learning on creative thinking skills in social studies maps of grade V students between students who use the mind mapping learning method and students who use conventional learning at SDN Bunder 4, Tangerang Regency. This study uses a Quasi Experimental research method, a type of pseudo-experimental research method using a Pretest – Posttest Control Group Design. Engaging class Involving an experimental class and a control class. In this study, students in the experimental class were taught using the mind mapping learning method with the teaching module of the independent curriculum of social studies subject matter, namely the appearance of nature. The results of the study showed that there was a significant influence on the creative thinking skills of grade V students who used the mind mapping learning method. The average score of the experimental class postes is 81,49 while the control class is 45,77. The colmigrov normality test and homogeneity test showed that the 2-tailed sig of 0.000 was smaller than α=0.005, indicating that there was a significant influence of the mind mapping learning method on the creative thinking skills of grade V students on the social studies maple.